Pengaruh Platform Wordwall terhadap Hasil Belajar Kekayaan Budaya Indonesia Siswa Kelas IV UPTD SDN Labang - Jasmine Assayyidah; Priyono Tri Febrianto (MASALIQ, 2025)
The lack of innovation in the use of instructional media during the teaching and learning process has contributed to low student achievement, with learning outcomes failing to meet the established criteria. This study aims to determine the significant effect of using Wordwall-based instructional media on the learning outcomes of fourth-grade students at UPTD SDN Labang in the topic of Indonesia’s cultural richness. A quantitative approach was employed using a quasi-experimental design in the form of a nonequivalent control group design. The sample was selected through total sampling, with data collected through interviews, observations, questionnaires, documentation, and learning outcome tests. The results showed that the average post-test score in the experimental class using Wordwall media was 76.45, while the control class using PowerPoint media scored an average of 64.6. An independent samples t-test yielded a significance value (Sig. 2-Tailed) of 0.001 < 0.05, indicating that H₀ is rejected and Hₐ is accepted. Thus, it can be concluded that the use of the Wordwall platform has a significant effect on improving student learning outcomes. The implications of this study suggest that utilizing interactive media such as Wordwall can serve as a strategic alternative for enhancing learning effectiveness at the elementary school level.